Homogeneously catalyzed depolymerization of lignin from organosolv medium: Characterization, optimization, and minimization of coke formation. (4th April 2021) - Süss, Raphaela; Kamm, Birgit; Arnezeder, David; Zeilerbauer, Lukas; Paulik, Christian
Abstract: This study focused on maximizing yields of oligomeric and monomeric products while minimizing coke formation in the depolymerization of lignin from an organosolv medium. A design of experiments (DoE) with temperature, time, and ethanol‐water ratio as factors was established and tested. Optimized reaction conditions were found at 185.4°C with 7.5 wt% sodium hydroxide as catalyst, an ethanol‐water ratio of 48.6% (v/v), and a residence time of 30 minutes. With these optimized parameters, maximum monomer and oligomer yields of 9.4 wt% and 86.2 wt% and minimized coke formation of 0.5 wt% were achieved. The oligomeric and monomeric products were characterized by GPC, GC‐MS, and OH‐group determination (Folin‐Ciocalteu).